2015
DOI: 10.1371/journal.pone.0123839
|View full text |Cite
|
Sign up to set email alerts
|

Catalases Induction in High Virulence Pinewood Nematode Bursaphelenchus xylophilus under Hydrogen Peroxide-Induced Stress

Abstract: Considered an EPPO A2 quarantine pest, Bursaphelenchus xylophilus is the causal agent of the pine wilt disease and the most devastating plant parasitic nematode attacking coniferous trees in the world. In the early stages of invasion, this nematode has to manage host defence mechanisms, such as strong oxidative stress. Only successful, virulent nematodes are able to tolerate the basal plant defences, and furthermore migrate and proliferate inside of the host tree. In this work, our main objective was to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…In the present study, antioxidant proteins were also identified in the secretome of B. xylophilus . These proteins have been proved as pivotal tools in protecting B. xylophilus from ROS and toxic compounds accumulated inside the pine trees3738.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, antioxidant proteins were also identified in the secretome of B. xylophilus . These proteins have been proved as pivotal tools in protecting B. xylophilus from ROS and toxic compounds accumulated inside the pine trees3738.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Siddique et al (2014) showed a positive role for H 2 O 2 in Arabidopsis susceptibility to cyst nematodes, indicating that nematodes can also induce ROS to promote infection. Correlations between nematode virulence and resistance to oxidative stress have been observed in the pinewood nematode, Bursaphelenchus xylophilus (Vicente et al , 2015). Together, these findings support the idea that the establishment of a cytoprotective mechanism against environmental oxidative stresses is a crucial prerequisite for successful PPN infection at both early and later time points after contact with the plant cell.…”
Section: Section I: Plant Basal Defence the Apoplast And The Redox Bmentioning
confidence: 99%
“…Similarly, nematode J2s that have not yet entered the root (pre-parasitic plant nematodes) also provide pronounced resistance to oxidative stress, correlating with their degree of virulence (Dubreuil et al , 2011; Vicente et al , 2015; Li et al , 2016). In fact, previous findings have reported the insulin/IGF-1 signalling (IIS) pathway as a mediator between development and stress responses following the model ‘ should I stay or should I go ’ (Schindler and Sherwood, 2014).…”
Section: Section Ii: Potential Key Regulators Of Oxidative Stress Resmentioning
confidence: 99%
See 2 more Smart Citations